2020
DOI: 10.21608/adjalexu.2020.79975
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Guided Implant Insertion in Mandibular Free-End Saddle Areas Using Stereolithographic Surgical Stent

Abstract: INTRODUCTION: The success of implant therapy depends primarily on appropriate treatment planning and properly performed implant placement surgery.Guided implant surgery (template based guided cavity preparation and guided implant insertion) is effective to guide the implant placement.This can be achieved by means of a surgical guide Stent.Stents are designed in conventional methods or stereolithography which allows the fabrication of surgical guides from 3D computer generated models for precise placement of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
(19 reference statements)
2
1
0
Order By: Relevance
“…This method has not been found in literature except in one study by Abd Alkader et al, 2020 [17} . Comparison between virtual and actual implants' distance to IAN showed a statistically significant difference, with a mean distance of 0.72 ± 0.25 mm for actual implants and 1.7 ± 0.56 mm for virtual implants, interpretation of this results raises an alarm that the distance of the actual implant to IAN is commonly lesser than that on virtual implants which could endanger the IAN if this was not considered in virtual planning. This finding actually coincides with that of Abd Alkader et al 2020 [17] who also found a significant difference in their comparison between virtual and actual implant distance to IAN as a means of CASG accuracy evaluation, but the reported values of this distance in their study (4.30 ± 2. 69 mm for virtual implants and 3.88 ± 2.23 for actual implants) were higher than those in ours.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This method has not been found in literature except in one study by Abd Alkader et al, 2020 [17} . Comparison between virtual and actual implants' distance to IAN showed a statistically significant difference, with a mean distance of 0.72 ± 0.25 mm for actual implants and 1.7 ± 0.56 mm for virtual implants, interpretation of this results raises an alarm that the distance of the actual implant to IAN is commonly lesser than that on virtual implants which could endanger the IAN if this was not considered in virtual planning. This finding actually coincides with that of Abd Alkader et al 2020 [17] who also found a significant difference in their comparison between virtual and actual implant distance to IAN as a means of CASG accuracy evaluation, but the reported values of this distance in their study (4.30 ± 2. 69 mm for virtual implants and 3.88 ± 2.23 for actual implants) were higher than those in ours.…”
Section: Discussionsupporting
confidence: 91%
“…When it comes to the horizontal deviation between actual and planned implant cervically; this study recorded a mean deviation of 1.15 ± 0.49 mm which was very close to the mean cervical deviation for clinical studies included in Bover-Ramos' meta-analysis (1.1 ± 0.09), it was also close to the those recorded by Di Giacomo et al 2012 [23] (1.26 ± 0.66 mm), Vieira et al 2013 [27] (1.42 ± 0.71 mm) and Abd Alkader et al 2020 [17] (0.96 ± 0.7 mm) in mandibular implants placed by mucosa supported stereolithographic CASG fixed with pins based on CBCT images. However, this cervical deviation is considered slightly higher than those recorded by Pettersson et al 2012 [24] (0.8 mm) in mandibular implants placed by mucosa supported selective laser sintering CASG fixed with pins based on CBCT images, and slightly lower than that recorded by Cassetta et al 2013 [30] (1.64 ± 71 mm) in mandibular implants placed by mucosa supported stereolithographic CASG fixed with pins based on MSCT images.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation